2023
DOI: 10.1007/s13346-023-01306-x
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived exosomes carrying siRNA-KEAP1 promote diabetic wound healing by improving oxidative stress

Abstract: Diabetic wounds are a serious complication of diabetes mellitus (DM) that can lead to persistent infection, amputation, and even death. Prolonged oxidative stress has been widely recognized as a major instigator in the development of diabetic wounds; therefore, oxidative stress is considered a promising therapeutic target. In the present study, Keap1/Nrf2 signaling was confirmed to be activated in streptozotocin (STZ)-induced diabetic mice and methylglyoxal (MGO)-treated human umbilical vein endothelial cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…19 In another study, researchers investigated the potential of miEVs as siRNA carriers to target the Keap1 gene for diabetic wound healing and found that their formulation increases collagen synthesis and neovascularization, which leads to the great healing of diabetic wounds in mice models. 137 Although unmodified miEVs have shown good potential for the delivery of various therapeutics, several studies have recently focused on the surface functionalization of miEVs to direct drugs precisely to the target tissue and thereby reduce off-target effects and increase efficacy 138,139 (Table 6). Because the folate receptor is overexpressed in various cancer cells, its ligand, folic acid (FA), has been used to target drug carriers.…”
Section: Intestinal Healthmentioning
confidence: 99%
“…19 In another study, researchers investigated the potential of miEVs as siRNA carriers to target the Keap1 gene for diabetic wound healing and found that their formulation increases collagen synthesis and neovascularization, which leads to the great healing of diabetic wounds in mice models. 137 Although unmodified miEVs have shown good potential for the delivery of various therapeutics, several studies have recently focused on the surface functionalization of miEVs to direct drugs precisely to the target tissue and thereby reduce off-target effects and increase efficacy 138,139 (Table 6). Because the folate receptor is overexpressed in various cancer cells, its ligand, folic acid (FA), has been used to target drug carriers.…”
Section: Intestinal Healthmentioning
confidence: 99%
“…These methods typically involve ultracentrifugation or other purification techniques to isolate the EVs from other milk components . One potential application of bovine milk-derived EVs is in the development of therapies for inflammatory diseases, such as inflammatory bowel disease and arthritis. , Studies have shown that mEVs can suppress inflammation and promote tissue repair in animal models of these diseases. In addition, mEVs have been shown to enhance the immune response in vitro, suggesting their potential as immunomodulatory agents .…”
Section: Origin and Function Of Evsmentioning
confidence: 99%
“…Extracellular vesicles have garnered significant interest as potential vehicles for drug delivery, due to their ability to transfer their contents between cells and tissues . Scientists are investigating ways to modify extracellular vesicles to target specific cells or tissues and to load them with therapeutic payloads such as drugs or genetic material. , The use of EVs as drug delivery systems has been hindered by several factors. One of the main issues is their low gastrointestinal stability, which makes it difficult for them to survive in the harsh environment of the digestive system .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, to relieve oxidative stress at diabetic wound sites, siRNA‐Keap1 (siKeap1) functionalized milk‐released sEVs were fabricated by ultrasonicating the mixed PBS solution of siRNA‐Keap1 and sEVs. SiKeap1‐enriched sEVs silenced Keap1 gene and increased the expression of antioxidant protein (HO‐1) in vitro and accelerated diabetic wound healing by promoting collagen formation and neovascularization 74 . Yerneni et al.…”
Section: Optimizing the Function Of Sevsmentioning
confidence: 99%
“…SiKeap1-enriched sEVs silenced Keap1 gene and increased the expression of antioxidant protein (HO-1) in vitro and accelerated diabetic wound healing by promoting collagen formation and neovascularization. 74 Yerneni et al loaded the antiinflammatory drug (curcumin, CA) inside sEVs with the assistance of albumin under milder sonication. The pre-introduction of albumin provided abundant bindingsites of CA inside sEVs.…”
Section: Cargo Characteristics Technical Processesmentioning
confidence: 99%